Simultaneous overactivation of Wnt/β-catenin and TGFβ signalling by miR-128-3p confers chemoresistance-associated metastasis in NSCLC - Junchao Cai (Nature Portfolio, 2017)
Chemoresistance and metastasis are tightly associated features in non-small cell lung cancer (NSCLC). Here, the authors show that resistant NSCLCs have high levels of miR-128-3p which promotes EMT and cancer stem cell survival through the modulation of both Wnt/B-catenin and TGF-β pathway.